2022
DOI: 10.3389/fpubh.2022.971487
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mental health among youths and adolescents in the digital era: Roles of cyber and traditional bullying, violence, loneliness, and environment factors

Abstract: IntroductionAlthough the pathogenesis of depressive disorders is not fully elucidated, untreated adolescent depression can lead to serious sequelae such as impaired academic performance and social functioning, substance use disorders, poor self-esteem, and increased risk for suicidal ideation and attempts. Literature on adolescent mental health in Vietnam is limited, despite increased international awareness of this critical issue. This study aimed to investigate the prevalence and associations of depressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The study identified early alcohol consumption as a major consequence of parental divorce, which contributes to an increased risk of mental health issues in children, particularly anxiety and depression [ 39 , 40 ]. Furthermore, bullying was strongly associated with a higher risk of depression, as demonstrated by studies in Vietnam [ 41 43 ]. Another study by Obeid et al [ 21 ] discovered that adolescents with divorced parents were relatively likely to experience social fear and avoidance, depression, and suicidal ideation.…”
Section: Discussionmentioning
confidence: 92%
“…The study identified early alcohol consumption as a major consequence of parental divorce, which contributes to an increased risk of mental health issues in children, particularly anxiety and depression [ 39 , 40 ]. Furthermore, bullying was strongly associated with a higher risk of depression, as demonstrated by studies in Vietnam [ 41 43 ]. Another study by Obeid et al [ 21 ] discovered that adolescents with divorced parents were relatively likely to experience social fear and avoidance, depression, and suicidal ideation.…”
Section: Discussionmentioning
confidence: 92%
“…In the end, teenagers feel that they are not sufficient to be showing their authentic self, based on what digital media influenced them [49]. Next, because of the background of their self-distrust facing the virtual world, they feel the need to be someone else [50]. It is this reason for self-confidence that makes new demands, that there is a need for knowledge about digital literacy and how to be a good citizen in virtual world so that they can be more confident socializing in the virtual world.…”
Section: Resultsmentioning
confidence: 99%
“…30 Bullies have low empathy for other people. Meanwhile, children who are victims of bullying based on research by Phan et al 38 are depressive, passive and shy.…”
Section: Lonelinessmentioning
confidence: 99%